2020
DOI: 10.20944/preprints202004.0094.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can Zinc Correction in SARS-CoV-2 Patients Improve Treatment Outcomes?

Abstract: The ongoing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic for which there is no established treatment available yet, has caused more than 68,000 deaths so far. Following the SARS-CoV outbreak in 2003, an Italian group described a hypothesis about the efficacy of two old drugs: Chloroquine (CQ) and Hydroxychloroquine (HCQ), against SARS-CoV and its future emergents. Later, this hypothesis was shown to be relevant in-vitro. Due to the high genetic similarity of SARS-CoV-2 and SARS-CoV, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Zn 2+ has an important place in a variety of infections: its deficiency predispose, whereas supplementation helps treat infections. It has been suggested that Zn 2+ correction combined with nCoV treatment sustains the antiviral activity, whereas reduces the cytokine storm and nCoV RNA synthesis [32]. These data indicate that inclusion of Zn 2+ with other drugs (such as CQ or HCQ) may be e beneficial in treatment of COVID-19.…”
Section: Zinc (Zn 2+mentioning
confidence: 86%
“…Zn 2+ has an important place in a variety of infections: its deficiency predispose, whereas supplementation helps treat infections. It has been suggested that Zn 2+ correction combined with nCoV treatment sustains the antiviral activity, whereas reduces the cytokine storm and nCoV RNA synthesis [32]. These data indicate that inclusion of Zn 2+ with other drugs (such as CQ or HCQ) may be e beneficial in treatment of COVID-19.…”
Section: Zinc (Zn 2+mentioning
confidence: 86%
“…Zn 2+ has an important place in a variety of infections: its deficiency predispose, whereas supplementation helps treat infections. It has been suggested that Zn 2+ correction combined with nCoV treatment sustains the antiviral activity, whereas reduces the cytokine storm and nCoV RNA synthesis [32]. These data indicate that the inclusion of Zn 2+ with other drugs (such as CQ or HCQ) maybe e beneficial in the treatment of COVID-19.…”
Section: Inhibitors Of Viral Proteasementioning
confidence: 87%
“…Parenteral zinc + chloroquine/hydroxychloroquine (CQ/HCQ) in the treatment of hospitalized COVID-19 patients may help to improve clinical outcomes and to limit the COVID-19 fatality rates. Therefore, whether zinc supplementation in combination with CQ/HCQ should be recommended for high risk or also younger patients outside of clinical trials as a prevention or treatment approach during SARS-CoV-2 pandemic, should be considered only on a case-by-case basis [39,40].…”
Section: Antiviral Activities Of Zn 2+ Ions For Adults With Preventiomentioning
confidence: 99%